When the Difference Sediments in Law: Interview with Gil Anidjar: Кога разликата ќе стане закон: Интервју со Гил Аниџар - Alagjozovski, Robert; Anidjar, Gil (Identities: Journal for Politics, Gender and Culture, 2006)
Author(s): Robert Alagjozovski and Gil Anidjar | Роберт Алаѓозовски и Гил Аниџар Title (English): When the Difference Sediments in Law: Interview with Gil Anidjar Title (Macedonian): Кога разликата ќе стане закон: Интервју со Гил Аниџар Translated by (English to Macedonian): Robert Alagjozovski | Роберт Алаѓозовски Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 5, No. 2 (Summer 2006) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 15-33 Page Count: 18 Citation (English): Robert Alagjozovski and Gil Anidjar, “When the Difference Sediments in Law: Interview with Gil Anidjar,” Identities: Journal for Politics, Gender and Culture, Vol. 5, No. 2 (Summer 2006): 15-33. Citation (Macedonian): Роберт Алаѓозовски и Гил Аниџар, „Кога разликата ќе стане закон: Интервју со Гил Аниџар“, превод од англиски Роберт Алаѓозовски, Идентитети: списание за политика, род и култура, т. 5, бр. 2 (лето 2006): 15-33.